Behavioral Accounting: Evaluating Policy and Academic Support Impact on Sustainable Green Mining Practices - Rismawati; Hamid, Rahmad Solling (Universitas Swadaya Gunung Jati, 2024)
This research examines the relationship among government policy, academic support, and the sustainable green economy in mining regions through the lens of behavioral accounting. Using a cross-sectional design with 201 stakeholders and structural equation modeling, findings show significant positive impacts of government policy and industry awareness on green practices, while community participation was not significant. Academic support modestly but significantly drives sustainability. Regulation from the central government did not significanly moderate these relationships, suggesting a possible disconnect with local invinitive. Limitations include the cross-sectional design and reliance on self-reported data, suggesting the need for longitudinal studies. The study underscores the importance of cohesive policies and the role of academic contributions and industry awareness in promoting sustainable mining practices.